media PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS WORDWALL UNTUK MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK KELAS V MIS PUI GEREBA - Husni Badruttamam; Hatma Heris Mahendra; Ade maftuh (STKIP Subang, 2025)
Education plays a crucial role in character building and the development of students' skills, and efforts to improve the quality of learning are vital to consider. One of the factors that support successful learning is the use of effective media. With the advancement of technology, the use of digital-based media such as Wordwall has become a viable option to enhance student motivation. This study aims to examine the effect of using Wordwall-based learning media on student motivation in grade V at MIS PUI Gereba, particularly in the subject of Pancasila education on rights and obligations. This research uses a Classroom Action Research (CAR) design, conducted in two cycles, with stages of planning, action implementation, observation, and reflection. The subjects of the study consisted of 18 students, divided into two groups based on their initial learning motivation. The results showed that the use of Wordwall media significantly increased student motivation, with a percentage increase from 44% in the pre-action phase to 66.67% in cycle I, and 88.89% in cycle II. This indicates that Wordwall media successfully created a more interactive and enjoyable learning environment, increasing student engagement in the learning process. Therefore, the use of technology-based learning media like Wordwall increase to improve the quality of education in elementary schools.